EDUKASI PEMANFAATAN PANGAN LOKAL DALAM RANGKA MENDORONG PENURUNAN ANGKA STUNTING DI KELURAHAN SUNGAI BESAR, KOTA BANJARBARU - Hastuti, Eny; Ismail, Hasan; Rizaldi, Gusti; Norhayati, Norhayati (Jurnal Abdi Insani, 2024)
Indonesia is one of the countries that has experienced a reduction in the incidence of stunting, from 30.8% in 2018 to 21% in 2022 and is targeted at 14% in 2024. Stunting is caused by a lack of nutritional intake in the first 1000 days of life. Based on a preliminary study in Sungai Besar Subdistrict, there is still a fairly high prevalence of babies below the red line which leads to stunting, which occurs at the age of 0 months to 4 years, as many as 17 toddlers. This community service aims to provide information and education regarding stunting and local food that can be used to prevent stunting with the hope of reducing stunting rates in the Sungai Besar subdistrict. Community service activities were carried out on April 30 2024 in the Sungai Besar Village Hall and via Zoom Meeting. Partners in this activity are PKK Sungai Besar cadres, Banjarbaru City. Information and education is provided using powerpoint and leaflet. The average pretest score of the participants was 6.375 while the posttest was 8. Based on the paired t-test, the significance value was 0.002 (<0.05), which shows that there is a significant difference between the pretest and posttest scores regarding understanding stunting and local food that can be used as prevention of stunting. Based on the average pretest and posttest scores, the percentage increase in understanding was 20%. Through this community service, it is hoped that participants can make efforts to prevent and utilize local food so that the reduction in stunting rates can be increased. Based on the results of the service activities carried out, it was concluded that the information and education carried out were able to increase participants' knowledge and understanding regarding stunting and its prevention using local food.